Efektivitas Program Percepatan Penurunan Stunting pada Balita dalam Pelayanan Kesehatan di Puskesmas Bojong Rawalumbu Tahun 2021 - Marcel Vianca Agustine (Journal of Islamic Studies & Social Science, 2024)
The stunting reduction acceleration program is a program established by the Decree of the Republic of Indonesia Presidential Regulation Number 72 of 2021 with a concern the Acceleration of Stunting Reduction. This study aims to determine the effectiveness of the program to accelerate the reduction of stunting in children under five years old (toddler) in health services at the Bojong Rawalumbu Health Center. To identify the acceleration of stunting reduction, the author uses the theory of program effectiveness proposed by Budiani, namely the accuracy of program targets, program socialization, program objectives and program monitoring. The research method used for this study is qualitative research. In addition, the tecniques used for data collection are observation, interviews and documentation that related to this research. The results of this study explain from the beginning of the implementation, stunting reduction acceleration program in health services at the Bojong Rawalumbu Health Center, the program has been running quite effectively based on the phenomenon of program targeting accuracy, program socialization, program objectives and program monitoring.